Immunotherapy of Allergic Rhinitis: New Therapeutic Opportunities with Virus-like Particles Filled with Cpg Motifs. Issue 3 (May 2013) - Klimek, Ludger; Schendzielorz, Philipp; Mueller, Philipp; Saudan, Philippe; Willers, Joerg
Background: The incidence of allergic rhinitis (AR) has increased constantly over the last decades. The disease can significantly lower quality of life and subsequently might progress to allergic asthma. Allergen-specific immunotherapy is mostly used to cope with the cause of the disease. However, incidence of systemic reactions or limited compliance hampers the widespread use of this therapeutic approach. Therefore, new candidates are examined to improve immunotherapy of allergies. Recently, a new technology was developed with the aim to positively influence the immune system of allergic patients. Virus-like particles (VLPs) represent a potent vaccine platform that has been proven to be immunogenic and clinically effective. To enhance immune cell activation, addition of Toll-like receptor ligands and/or depot-forming adjuvants seems to be helpful. In this context, CpG motifs represent intensive investigated and potent stimulators of T cells. This article focuses on the function of VLPs and CpG motifs and their clinical experience for treatment of AR. Methods: A literature review was performed. Results: Several published studies showed a beneficial impact of the treatment on allergic symptoms. They tested VLPs filled with or without CpG motifs in combination with or without allergen. Conclusion: Results encourage further investigations of VLPs and CpG motifs as adjuncts to or even alternative candidates for immunotherapy of allergic disorders.